2022
DOI: 10.33545/surgery.2022.v6.i2b.902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phytotherapy in Plantago major and Solanum aculeastrum vs a-blocker treatment of benign prostate hyperplasia by using ipss, clinic and ultrasound in Goma

Munyantwari AE,
Swedi ME,
Kasali MF
et al.

Abstract: Herbal medicine is an ancient or millennium practice. The World Health Organization has recognized its practice for several decades. The present study is motivated by the decrease of patients with voiding disorders in the consultation of the hospitals of Goma, apart those with acute urinary retention. Yet, it was noted their presence in number in the traditional practitioner. Benign prostatic hyperplasia, an essential cause of voiding disorders in elderly men, has been the beneficiary of herbal medicine around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Methods: all these patients had benefited from a prior histopathological examination in the previous study, which confirmed BPH. It is currently a question of evaluating by the clinic (IPSS-QdV, TR) and the paraclinical (PSA, ultrasound) in the same way as for the first study [19] . So we used 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods: all these patients had benefited from a prior histopathological examination in the previous study, which confirmed BPH. It is currently a question of evaluating by the clinic (IPSS-QdV, TR) and the paraclinical (PSA, ultrasound) in the same way as for the first study [19] . So we used 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study presented by us, they had appeared from the 14th day but confirmed at the 1st check-up (one month). While conventional medical treatment for BPH is known to be lifelong and susceptible to side effects, improvement with Plantago major and Solanum aculeastrum phyto-medication was noted over the 27 months of the study without any toxicity [19,20] .…”
Section: Introductionmentioning
confidence: 99%